Diagnostic criteria for temporomandibular disorders (DC/TMD): interexaminer reliability of the Finnish version of Axis I clinical diagnoses. (6th May 2017) - Leskinen, J.; Suvinen, T.; Teerijoki‐Oksa, T.; Kemppainen, P.; Näpänkangas, R.; Alstergren, P.; Le Bell, Y.; Forssell, H.; Myllykangas, R.; Tolvanen, M.; Doepel, M.; Sipilä, K.
Summary: Recently, updated diagnostic criteria for temporomandibular disorders (DC/TMD) were published to assess TMD in a standardised way in clinical and research settings. The DC/TMD protocol has been translated into Finnish using specific cultural equivalency procedures. To assess the interexaminer reliability using the Finnish translations of the DC/TMD‐FIN Axis I clinical diagnostic assessment instruments. Reliability assessment data were collected during a 1‐day DC/TMD Examiner Training Course at the University of Turku, Finland, in collaboration with the International DC/TMD Training and Calibration Center in Malmö University. Clinical TMD examinations according to the Finnish pre‐final version of the DC/TMD Axis I assessment protocol were performed by four experienced TMD specialists on altogether 16 models. Kappa coefficient, overall percentage agreement (%A) as well as positive (PA) and negative (NA) agreements were used to define the reliability. Myofascial pain with referral, headache attributed to TMD and disc displacement (DD) without reduction without limited opening showed excellent kappa values (range 0·87–1·00). Fair‐to‐good reliability was observed for diagnoses of myalgia (k = 0·67), arthralgia (k = 0·71) and DD with reduction (k = 0·64). The PA was high for all pain‐related diagnoses and DD without reduction without limited opening (medians ≥83%), and acceptable for DD with reduction (median 67%). The NA was high (medians ≥87%) for all DC/TMD diagnoses, except for myalgia which showed acceptable NA (median 75%). The %A was high for all assessed diagnoses (medians >85%). The findings of this study showed DC/TMD‐FIN Axis I to demonstrate sufficiently high reliability for pain‐related TMD diagnoses.